Estudo do processamento temporal em indivíduos com gagueira - Ferreira, Thaís Nunes Machado (2018)
Stuttering is a multidimensional and complex fluency disorder that has a genetic and neurofunctional basis. It presents numerous etiological factors that interact in a complex way and that, when associated, may have a direct relation. As an example of biological factors, the auditory abilities stand out as a factor that can interfere in the fluency of the speech. Therefore, the presence of disfluencies can be interconnected with temporal imprecision in speech perception, since fluent speech occurs from the interaction of acoustic aspects. As well, temporal processing skills can be considered as the basis of auditory processing, since many of the characteristics of auditory information are influenced by time. The focus of the present study was to identify not only the studies that have been demonstrating the relationship between auditory processing and stuttering, but also which temporal auditory processing abilities are altered in individuals with stuttering through auditory behavioral tests. Two articles were developed, the first corresponds to a Systematic Review, and the second to an Observational Study Article. The systematic review aimed to systematically review the scientific research that relates the temporal processing skills and speech fluency of individuals with stuttering. The second article evaluated 34 individuals (17 stuttering patients and 17 volunteers without stuttering or speech disorder) and showed that the "resolution and temporal ordering" abilities in stuttering individuals presented altered results. It is concluded that stuttering is associated with the presence of temporal changes, reinforcing the importance of including the evaluation of temporal auditory processing skills in the diagnosis of dysfluences.